The Influence of Sharia Financial Literacy and Perceived Usefulness on the Decision of the Muslim Generation to Choose the Shopee Paylater - Suherman, Andini Cahyaning; Subagio, N. Ari; Mahardiyanto, Agus (Tasharruf: Journal Economics and Business of Islam, 2024)
This research is motivated by the use of Shopee Paylater which is one of the most popular services. This attraction is a challenge for the Muslim generation to choose a payment method in online transactions that does not deviate from sharia principles. As data presented by CNBC Indonesia states that the younger generation was recorded as the largest contributor to paylater non-performing loans as of April 2023 at 9.7%.Islamic financial literacy is a guide for the community in managing finances in line with sharia principles. And perceived usefulness is a person's description of the usefulness of technology service products for one's performance. So the purpose of this study is to analyze the effect of Islamic financial literacy and perceived usefulness on the decision to choose the Shopee Paylater payment method. This research uses quantitative research. The data analysis method used is multiple linear regression analysis with the SPSS 25 analysis tool. The results of this study indicate that Islamic financial literacy has a significant negative effect on the decision to choose the Shopee Paylater payment method and perceived usefulness has a significant positive effect on the decision to choose the Shopee Paylater payment method. This means that if someone has a high level of Islamic financial literacy, the decision to choose Shopee Paylater will decrease. And if someone has a good perceived usefulness of using Shopee Paylater, the decision to choose Shopee Paylater will increase. So that efforts that need to be made to overcome the phenomenon of high rates of non- performing loans for the younger generation are increasing Islamic financial literacy and educating the public on the wise use of technology.